Tri‐typing of hepatitis B‐related acute‐on‐chronic liver failure defined by the World Gastroenterology Organization. Issue 1 (1st July 2020) - Tang, Xiaoting; Qi, Tingting; Li, Beiling; Li, Hai; Huang, Zuxiong; Zhu, Zhibin; Tu, Minghan; Gao, Jie; Zhu, Congyan; Jiang, Xiuhua; Yu, Xutong; Lu, Guanting; et al.
Abstract: Background and Aim: Tri‐typing of acute‐on‐chronic liver failure (ACLF), as proposed by the World Gastroenterology Organization (WGO), has not been validated in patients infected with hepatitis B virus (HBV). We aim to compare the three types of ACLF patients in clinic characteristics. Methods: Hospitalized ACLF patients with chronic hepatitis B from five hepatology centers were retrospectively selected and grouped according to the WGO classification. For each group, we investigated laboratory tests, precipitating events, organ failure, and clinical outcome. Results: Compared with type‐B ( n = 262, compensated cirrhosis) and type‐C ( n = 129, decompensated cirrhosis) ACLF, type‐A patients ( n = 195, non‐cirrhosis) were associated with a younger age, the highest platelet counts, the highest aminotransferase levels, and the most active HBV replications. HBV reactivation were more predominant in type‐A, while bacterial infections in type‐B and type‐C ACLF cases. Liver failure (97.4%) and coagulation failure (86.7%) were most common in type‐A compared with type‐B or type‐C ACLF patients. Kidney failure was predominantly identified in type‐C subjects (41.9%) and was highest (23/38, 60.5%) in grade 1 ACLF patients. Furthermore, type‐C ACLF showed the highest 28‐day (65.2%) and 90‐day (75.3%) mortalities, compared with type‐A (48.7% and 54.4%, respectively) and type‐B (48.4% and 62.8%, respectively) ACLF cases. Compared with type‐A (11.7%) ACLF patients, the increased mortality from 28 to 90 days was higher in type‐B (31.6%) and type‐C (37.5%). Conclusion: Tri‐typing of HBV‐related ACLF in accordance with the WGO definition was able to distinguish clinical characteristics, including precipitating events, organ failure, and short‐term prognosis in ACLF patients.